Heavy metals and gold in waters, sediments and aquatic vegetation from the Hauraki goldfields area of New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Geochemistry at Massey University - Sabti, Hutham (Massey University, 2000)
The Hauraki Goldfields area and the distribution of the heavy metals and gold from this goldfield area are reviewed. The current environmental impact of base metal mining at the Tui Mine, Te Aroha and gold mining near Waihi, was investigated by analysis of local waters, stream sediments, and aquatic vegetation. Analysis of waters from the Tui and Tunakohoia Streams showed concentrations of arsenic, cadmium, lead and zinc above recommended levels for potable water in the upper parts of these waterways. The discharge of these streams into the Waihou River (sampled upstream from Te Aroha and downstream to past Paeroa) did not have any significant effect on heavy-metal concentrations in this river. Aquatic macrophytes sampled in the Waihou, Ohinemuri and Waitekauri Rivers had very high heavy-metal concentrations compared with the ambient water and should be considered as potentially useful for assessing the impact of low-metal fluxes into the waters. Gold was determined in sediments from the Ohinemuri and Waitekauri Rivers along with other heavy metals derived from sulphide mineralisation at Waihi and Waitekauri. Gold was detected in aquatic macrophytes from streams draining both the Martha Mine at Waihi and the Golden Cross Mine at Waitekauri and indicated the possibility of prospecting for gold by analysis of these plants. X-ray diffraction analysis of heavy metal fractions in stream sediments showed the presence of pyrite in the upper reaches of the Tunakohoia and Tui Streams that drain the mineralised reefs and Tui tailings dam. Relatively immobile lead (galena) was retained close to the source, whereas copper and zinc minerals were more mobile and distributed further downstream from the areas of mineralisation. The relative mobilities of gold, copper, cadmium, lead and zinc from the Tui tailing dam (a serious environmental concern) were assessed by elution of these metals from columns containing 600 g of tailing, eluted with water, ammonium thiocyanate or ammonium thiosulphate. These elutions were carried out with, or with out, amendments. When eluted with water, the heavy metals showed a mobility sequence in the order copper, cadmium, zinc, lead, gold. After elution with 0.2% ammonium thiocyanate, there was a reduced mobility of zinc, copper and cadmium compared with the water elution and increased mobility of gold, Ammonium thiocyanate is specific in solubilising gold. Lead showed enhanced mobility, perhaps due to formation of the soluble complex ion Pb(CNS)4 2-. Mobility for zinc was enhanced by ammonium thiosulphate. A laboratory investigation on foam flotation was undertaken on gold, zinc, copper, lead, and cadmium in waters. A range of variables involved at their separation from dilute solutions by batch foam flotation technique was studied. I have recently developed a method of adsorbing colloid flotation in order to concentrate gold from natural waters into a very small volume of foam prior to quantification by GFAAS. Adsorbing colloid flotation (ACF) is a separation technique with distinct advantages for removing trace elements from natural and industrial waters. These advantages are: rapid processing, simple design, small volume of final solution, low residual concentration, flexibility of operation, and moderate cost. In this method, the substance to be removed (e.g. metal ions) is adsorbed on colloidal particles or coprecipitated on a floc produced by the addition of a flocculating agent. A surfactant is then added to adsorb on the particle or floc thus rendering it hydrophobic. The metal-loaded particle is then removed by further adsorption at the surface of rising bubbles in a flotation system. Experiments were carried out by use of a 52 mm diameter, 620 mm long glass column using a glass frit of pore size 20-40 μm for bubble generation. Cetyltrimethylammonium bromide (CTAB) a cationic surfactant, and thiourea (a complexing agent) were used either individually or in combination for removal of gold. The heavy metals included (Zn, Cu, Cd, and Pb) removed by dodecyl sulfate-Na salt (NaDS) and sodium oleate(NaO). The electrolyte tolerance of adsorbing colloid flotation of heavy metals ions (Pb2+ , and Cd2+ ) from waste water was improved significantly by use of the Fe(OH)3 and NaLS (sodium laurylsulfate) system for lead removal or A1(OH)3 and HTMABr (hexadecyltrimethylammonium bromide) system for cadmium removal. Extraction of the gold into the foam layer was strongly dependent on the pH of the feed for which pH 11 was optimum. Adding 10 mg/L of thiourea to an equal volume of CTAB instead of CTAB alone, increased the extraction of gold to a dramatic degree. A distribution coefficient (Kd ) of 46,000 was achieved under optimum conditions. The percentage extraction reached 99%. The method was applied to a number of natural waters draining gold mines and the Tui base metal mine in the Hauraki Goldfields region. Gold values reflected the presence of mineralization in the stream and river samples. It was concluded that the method may have some use in hydrogeochemical prospecting for gold. Examples are given for the laboratory separation by foam flotation techniques of gold, zinc, copper, lead, and cadmium ions from a solution . Different technological variables that affect the process were investigated, such as concentration level, pretreatment required, pH effect, etc.
Keywords: Mineral industries; Environmental aspects; Geochemistry; Water Pollution; New Zealand; Hauraki District; Matamata Piako District; Gold mines and mining; Heavy metals -- Absorption and adsorption